Beneficios técnico-económicos del cambio de tipo de broca y martillo dth de la serie ql60 por la serie nd680 en la perforación de los taladros de producción del tajo san pedro, minera la zanja - Valderrama Garcia, Deiby Nelber (2018)
The company BH Rock Tools constantly applies a process of continuous improvement in all the solutions offered to the mining market. This in order to increase the profitability of its customers and to expand to most possible projects both nationally and internationally. Such is the current case of La Zanja mining with whom he has been working since 2016. Currently, the use of QL60 series drilling steels has presented some deficiencies in terms of compliance with performance indicators and technical work in them. All this generates that you have a longer time of operational delays, a low drilling speed and therefore a higher cost per meter drilled. BH Rock Tools chose the ND680 series to improve the current performance indicators in the mine. This consists of a hammer manufactured based on the principle of mirror impact technology, much more convex drills and with a greater number of spherical inserts in them, thus allowing the optimization of the unit drilling process. At the end of the tests carried out with the ND680 series, a significant reduction of 3.9% in the operational delays was obtained, an increase in the drilling speed of 9%, going from 59.4 to 64.7 m/h and a significant reduction of 8.1% in the TDC going down from 4.37 to 4.02 $/m. This could generate, if you decide to continue with your employment, a significant monthly and annual savings of $ 3,390.47 and $ 40,685.69 respectively.